Efeito de diferentes tipos de meio suporte no desempenho de filtros biológicos percoladores aplicados ao pós-tratamento de efluentes de reatores UASB, com ênfase na nitrificação - Paulo Gustavo Sertorio de Almeida (2007)
The research aimed at investigating the performance of different types of packing media used in trickling filters applied to the post-treatment of effluents from UASB reactors, focusing on ammonia removal. The performance of the TFs operating without secondary settlers wasinvestigated, in relation to organic matter removal. The experimental apparatus consisted of one UASB reactor (22 m³) and four trickling filters operating in parallel. Each TF was filled with a different type of packing media: blast furnace slag; random plastic rings; Downflow Hanging Sponge (DHS) and pieces of plastic tubing. Ammonia concentration in the effluent was higher than 20 mgNH4-N/L when the TF wereoperated with an organic loading rate (OLR) of 0.43 kgBOD/m³.d and a surface loading rate (SLR) of 20 m³/m².d. For these operating conditions, no statistical differences were identified between the four types of packing media, as indicated by the Kruskal-Wallis tests. When theTF were operated with an OLR of 0.24 kgBOD/m³.d and a SLR of 10 m³/m².d, the ammonia concentration in the effluent was lower than 20 mgNH4-N/L, and statistical differences between the packing media were detected. These results indicate that the type of packing media can affect the nitrification process. According to the profiles of physical-chemicalparameters associated with nitrification, it was observed that the nitrification occurred when BOD/TKN ratio was between 0.30 and 0.60, and soluble BOD was around 15 mg/L. Regarding the removal organic matter without the use of secondary settlers, the TF post- UASB were able to meet the local discharge standards for BOD (60 mg.L-1) and COD (90 mg.L-1) in approximately 100% of cases, when operated with OLR of 0.43 and 0.24 kgBOD.m-3.d-1 and SLR of 20 and 10 m3.m-2.m-1, respectively. However, the discharge standard for TSS (60 mgTSS/L) was not consistently met when the TF were operated at the higher OLR and SLR. In general, the expansion of the functional aspects of TFs post-UASB to meet nitrification can simplify the typical flow sheets of these systems, since the operational conditions for nitrification are the same that lead the TF without secondary settlers to produce BOD, COD and TSS concentrations below the discharge standard established bythe Brazilian legislation. In this case, the main advantage is that the management of aerobic sludge is not necessary.